Korean Popular Culture as A ‘Lethal Weapon’: A Journey Toward Nation Branding of The Republic of Korea - Abidin, Zainal; Mayasari, Mayasari; Utamidewi, Wahyu; Tayo, Yanti; Nursanti, Siti (Faculty of Social and Political Sciences, Universitas Diponegoro, 2024)
(Korean Popular Culture as A ‘Lethal Weapon’: A Journey Towards Nation Branding of the Republic of Korea) The crisis that occurred in 1997 was experienced by the Republic of Korea as a sign that today the Republic of Korea has become a developed country. The government of the Republic of Korea took the initiative to borrow funds from the IMF for the first time in the history of Korea. The Republic of Korea's turnaround process was revived from adversity due to the impact of the crisis, which led to a day called